Association between preoperative serum albumin and long-term all-cause mortality after percutaneous vertebroplasty for vertebral compression fracture - Yu-Tsung Lin; Wen-Chien Wang; Yu-Hsien Lin; Yun-Che Wu; Kun-Hui Chen; Chien-Chou Pan; Ching-Heng Lin; Jun-Sing Wang; Cheng-Hung Lee (PLoS ONE, 2026)
Purpose Albumin levels have demonstrated superior predictive value for surgical outcomes across a variety of surgeries. However, their effect on long-term survival after vertebroplasty for vertebral compression fracture has not yet been well studied. This study aims to investigate the relationship between preoperative albumin levels and long-term survival in patients who underwent percutaneous vertebroplasty for vertebral compression fractures. Materials and methods We enrolled patients who underwent vertebroplasty for vertebral compression fracture between the period of May 1, 2013 to June 30, 2020 in a single medical center. Patients who were diagnosed with a pathologic compression fracture, underwent additional spinal instrumentation during the same surgery, and those without data regarding their bone mineral density (BMD) were excluded. Cox proportional hazard models were conducted to examine the effects of hypoalbuminemia (<3.5 g/dL) on all-cause mortality after adjusting for age, gender, body mass index, smoking, diabetes, hypertension, chronic kidney disease (CKD), osteoporosis. Results A total of 145 patients were analyzed, and the median follow-up period was 2.12 (interquartile range 1.51–3.28) years (mean follow-up 2.65 [SD 1.78] years). Compared with normal albumin levels, patients with hypoalbuminemia were found to be independently associated with a higher risk of all-cause mortality (hazard ratio 3.154, p = 0.014). These findings remained significant when albumin was examined as a continuous variable (hazard ratio 0.242, p = 0.001) and even after multivariate adjustment as well (hazard ratio 0.192, p = 0.004). Conclusion Hypoalbuminemia was associated with all-cause mortality among patients who underwent vertebroplasty for vertebral compression fractures. Our findings highlighted the impact of nutritional status on long-term mortality in an elderly surgical population.